2014
DOI: 10.4236/jcdsa.2014.45040
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Efficacy of Product Containing “Skin Calm Complex” <i>in Vitro</i> Reconstructed Epidermis

Abstract: Atopic dermatitis is classified as a chronic inflammatory skin disease, which is characterized by alterations in barrier function and immune system of the skin. In a previous study, the efficacy of REPAVAR ATOPIC SKIN BODY CREAM EXTREME (a product containing "SKIN CALM COMPLEX") on the epidermal barrier structure was demonstrated. However, the product has also been formulated to improve inflammation and itching. The aim of this study is to analyze product effectiveness on skin inflammation and itching which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The European Union Reference Laboratory for Alternatives to Animal Testing (EC-VAM) introduced validated test tests for acute irritation potential from exposure to acutely irritant substances contained in various products using EpiSkin, EpiDerm SIT, Modified Epiderm and SkinEthic models (ECVAM). Studies on the activity of pro-inflammatory cytokines such as interleukins have been reported [33][34][35][36]. However, we were unable to locate literature reports on the use of these materials for determination of modulation of the AA inflammation pathway, the key target of topically delivered NSAIDs.…”
Section: Current Models Of Determining Skin Inflammation Modulationmentioning
confidence: 99%
“…The European Union Reference Laboratory for Alternatives to Animal Testing (EC-VAM) introduced validated test tests for acute irritation potential from exposure to acutely irritant substances contained in various products using EpiSkin, EpiDerm SIT, Modified Epiderm and SkinEthic models (ECVAM). Studies on the activity of pro-inflammatory cytokines such as interleukins have been reported [33][34][35][36]. However, we were unable to locate literature reports on the use of these materials for determination of modulation of the AA inflammation pathway, the key target of topically delivered NSAIDs.…”
Section: Current Models Of Determining Skin Inflammation Modulationmentioning
confidence: 99%